Effect of stunting prevention education program through instagram on literacy and attitude of pre-marital couples - Titih, Huriah; Yuniarti, Falasifah Ani; Abdul Hamid, Siti Hazariah (Afarand Scholarly Publishing Institute; Turkey, 2023)
Aims Interconnected factors can cause increased stunting cases. One of the risk factors for stunting is adolescents’ lack of knowledge and attitudes. Various media, including Instagram, can be the reason behind the issue. This study aimed to determine the effect of providing the pre-marital education program through Instagram to increase the literacy and attitude of pre-marital couples regarding stunting prevention. Materials & Methods This quasi-experimental research with a pre-test and post-test design with a control group was conducted in pre-marital couples in the Gunung Kidul Regency from December 2021 to January 2022. The instruments were questionnaires (Google Forms) and educational media such as posters and videos via Instagram. Data were analyzed using the Wilcoxon and Mann-Whitney tests. Findings After receiving the pre-marital education program through Instagram, pre-marital couples were stunted in both the intervention and control groups. There was an increase in attitude in the intervention group after the intervention. The literacy and attitudes about stunting prevention were increased in pre-marital couples of the intervention compared to the control groups after being given pre-marital education through Instagram. Conclusion The pre-marital education program improves the literacy and attitudes about stunting prevention in pre-marital couples.